The Middle East and North Africa : Cauldron of conflict - James M. Dorsey (2014)
The Middle East and North Africa is a cauldron driven by sectarian and ethnic animosities. Winning the existential battle requires acknowledgement that the region’s states are multi-religious and multi-tribal entities. It demands a shift in mindset to overcome deep-seated fears and seek solutions to which all are parties.